Pandemi dan Stres: Menemukan Keseimbangan Antara Distress dan Eustress di Era “Work-from-Home” - Siti Patimah; Yuyun Yunita (Journal of Education and Teaching (JET), 2024)
This study aims to explore mental stress among lecturers and staff at Islamic Higher Education Institutions in Lampung Province during the COVID-19 pandemic and to identify effective stress management strategies. Using a literature review and interviews, the research gathered data from lecturers and staff to identify the main challenges they face, including increased workload, adjustment to remote work, and additional demands in the context of online learning. Interview results indicate that changes in work methods and lack of institutional support significantly contribute to stress. Lecturers experience stress due to adapting to unfamiliar technology, while administrative staff struggle with separating work from personal time. The study recommends enhancing technological capacity, providing psychosocial support, adequate training, and more flexible policies as solutions to reduce mental stress. The findings aim to help higher education institutions better manage and support the well-being of their academic staff.